Research on remote interference analysis and solution for 5G - Yujie LI (Dianxin kexue)
Remote interference mainly comes from the atmospheric ducting transmission.It is one of the reasons for the deterioration of the fifth-generation new radio (5G NR) mobile networks.Based on the analysis of the generation mechanism for the remote interference, two solution schemes were accordingly described for the remote interference management.The static increase GP (guard period) scheme was verified in the 5G NR network in areas with high atmospheric wares.Network operation data shows that the increasing guard period could avoid remote interference efficiently and thus improve the quality of the fifth-generation new radio networks.